Physical Characteristics of Antidesma spp. (Phyllanthaceae) Bogor Botanical Garden Collection - Umami, Riza; Husaini, Iin Pertiwi A; Putri, Irma Leilanai Eka (Jurnal Biologi Tropis, 2025)
Indonesia has a strategic position that supports high biodiversity and produces a variety of medicinal plants. Antidesma is one of the plants widely known in traditional medicine. This study aims to describe the morphological characteristics of antidesma, especially in the collection at the Bogor Botanical Gardens. This study was conducted at the Center for Applied Botany Research, BRIN, West Java, from November to December 2023. This study successfully identified eight species of Antidesma, namely Antidesma montanum var. Salicinum (Ridl.) Petra. Hoffm, Antidesma montanum Blume, Antidesma minus Blume (Euph.), Antidesma neurocarpum Miq., Antidesma stipulare Blume, Antidesma bunius (L.) Spreng, Antidesma tetrandum Blume, and Antidesma tomentosum Blume. Morphologically, Antidesma is a shrub to a woody tree with a round stem and crusty bark. The leaves are single, pinnate, and have smooth edges. The fruit is a drupe (bun) that ripens purplish-black, with a combination of sour, bitter, and sweet flavors. This discovery is important for species identification, exploration of local uses, and plant breeding programs to preserve Indonesia's native diversity and potential.